Learning the Deep Approach: Language Teachers' Voices - Karaman, Cendel; Okten, Celile; Tochon, Francois V. (UNIV GRANADA, 2012)
Based on the Deep Approach and learning modules prepared for Turkish as a Foreign Language, this qualitative study analyzed the experiences of instructors working at five research universities in the United States and one university in Turkey. The focus was on understanding how the implementation of the new approach was negotiated by teachers as they reflected on pedagogies. As a result of the interpretive analysis, we identified three main themes. This article presents how teachers' practices, professional and cultural identities, and transformations in learning and teaching emerged during the process of employing the deep approach.
Keywords: Teacher education; deep approach; identity; pedagogy; Turkish; language teachers; Education & Educational Research; Linguistics